ANALISIS FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KUNJUNGAN POSYANDU LANSIA PUSKESMAS AIR TELUK KIRI KECAMATAN TELUK DALAM KABUPATEN ASAHAN TAHUN 2023 - Erlina, Betti Beti (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2024)
Senior citizens are those aged 60 years and over. The increase in the elderly population is in line with data on the morbidity rate of the elderly population in Indonesia which tends to increase from year to year and is in line with the morbidity rate of the elderly population of 31.11% and the latest data in 2020 the number of elderly deaths consisting of 14,764 men (57.32 %) and 10,994 women (42.68%). Elderly Posyandu (elderly Posyandu) is an integrated health service for the elderly in a certain area that has been agreed upon. Posyandu aims to increase the range of health services for the elderly so that health services are formed that suit the needs of the elderly. The purpose of this study was to analyze the factors associated with visiting the elderly posyandu at the Air Teluk Kiri Health Center, Teluk Dalam District, Asahan Regency in 2023. The research design uses observational analytic methods through a cross sectional approach. The study population was 1059 people, with a total sample of 91 pregnant women using the proportional stratified random sampling method. The research instrument is a questionnaire. Data analysis methods are univariate, bivariate and multivariate with the chi square test. The results showed that there was a significant relationship between age (p<0.000 OR= 21 13.765 (95% CI: 4.089-46.341), education (p<0.001 OR= 4.821 5.455 (95% CI: 2.132-13.957), knowledge (p <0.010 OR= 4.708 3.450 (95% CI: 1.422-20.41), facilities and infrastructure (p<0.007 OR= 3.864 (95% CI: 1.517-9.840) and family support (p<0.009 OR= 3.563 (95% CI: 1.450-8.753). It was concluded that age, education, knowledge, facilities and infrastructure, and family support had a significant relationship with visits to the elderly Posyandu. Age is the most dominant factor associated with visiting the elderly Posyandu.